Inflammatory Disorders of the Nervous System Pathogenesis, Immunology, and Clinical Management - Minagar, Alireza; Alexander, J. Steven; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana Press, 2017)
This thoroughly updated edition covers all clinical aspects of neuroinflammation. The latest developments in pathogenesis and advances in treatment are provided, along with an understanding of the immune system's role and interactions between the activated immune cells, cerebral endothelial cells, and other main components of the immune cascade. Cutting-edge and authoritative, this volume offers practitioners a valuable resource for research and clinical practice.
Emerging Roles of Endothelial Cells in Multiple Sclerosis Pathophysiology and Therapy -- Multiple Sclerosis: Clinical Features, Immunopathogenesis and Treatment -- HIV infection of human nervous system: neurologic manifestations, diagnosis, and treatment -- Central nervous system vasculitis: Immunopathogenesis, clinical aspects, and treatment options -- Neurosarcoidosis: Clinical features, pathogenesis and management -- Cell-derived Microparticles / Exosomes in Neuroinflammation -- Acute disseminated encephalomyelitis: Clinical features, pathophysiology and clinical management -- Autoimmune encephalitis: Clinical features, pathophysiology and treatment -- Neuromyelitis optica: Immunopathogenesis, clinical manifestations, and treatments -- Immunopathogenesis and treatment of Guillain Barre Syndrome and Chronic Inflammatory Demyelinating Polyneuropathy -- Myasthenia gravis: Clinical features, immunology and therapies -- Idiopathic Inflammatory Myopathies -- The venous connection: the role of veins in neurodegenerative disease.
Keywords: Medicine; Neurology; Medicine & Public Health; Neurology